Laser induced nano‐porous Ti–O‐layers for durable titanium adhesive bonding. Issue 12 (10th December 2014) - Specht, U.; Ihde, J.; Mayer, B.; von Hehl, Axel; Weise, Jörg
<x xml:space="preserve">Abstract</x> For the integration of titanium in lightweight construction, adhesive bonding technology offers several advantages. Required wet‐chemical surface pre‐treatments of titanium are associated with high process effort, often harmful waste and in most cases insufficient durability of the adhesive bonds. In the present work, titanium is pre‐treated by an Nd : YAG laser (λ = 1064 nm), whereby a stable nanostructured oxide layer is generated. This layer provides a significant surface enlargement for durable adhesive bonding. The growth mechanism of such nano‐structures was examined by means of analytical methods.